The German Sport Satellite Account: Methodological basis and results for theperiod 2010 to 2019. - Gerd Ahlert; Sven Repenning (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2024)
The German Sport Satellite Account (SSA) is a robust statistical framework for measuring the economic importance of sport. The national SSA refers to the Vilnius Definition of Sport and makes sport-related transaction visible within the National Accounts. It measures the direct economic impact of sport on national income and employment. This GWS Research Report presents some of the key findings of the national 'SSA Monitoring Research Project' for the reporting period 2010 to 2019. This monitoring for Germany makes an important contribution to the provision of reliable and comprehensible data for evidence-based advice on sport policy and practice. The national SSA dataset gives an up-to-date picture of the diversity of the sport industry with its main activities, products and financing structures. It provides valuable insights concerning the demand-side of sport and the expenditure pattern due to active sport activities and passive interest in sport and presents supplemental sport-sociological information (i.a. sport participation by types of sport resp. sporting activities, age groups, income groups). The national SSA contributes to the economic underpinning of sport-policy decisions and decisions in enterprises, sport clubs and associations (e.g. public sport funding, hosting of sport events, advertising and sponsorship budgets, invest-ment decisions).
Keywords: 330; Sport Satellite Account (SSA); Vilnius Definition of Sport; satellite accounts; direct economic impact of sport; sport-related GDP; sport-related employment; sport-related consumption